Dissociative Experiences Mediate the Relationship Between Traumatic Life Events and Types of Skin Picking. Findings From Non-clinical Sample - Kłosowska, Joanna; Antosz-Rekucka, Rachela; Kałużna-Wielobób, Alina; Prochwicz, Katarzyna (Frontiers in Psychiatry, 2021)
Aim: Skin-picking (excoriation) disorder is considered as a form of maladaptive coping methods used by individuals who have difficulties in applying more adaptive strategies. Skin-picking development has been suggested to be preceded by traumatic life events. Dissociative symptoms have been reported as experienced by skin-picking sufferers during picking episodes. The purpose of the study was to examine whether the link between trauma and automatic type of skin-picking is mediated by the frequency of dissociative experiences, and whether the COVID-19 pandemic conditions have changed this relationship in any way. Methods: The study sample consisted of 594 adults (76% women) aged from 18 to 60. Traumatic life events, dissociative experiences, and types of skin-picking (focused vs. automatic) were assessed with self-report questionnaires. Mediation analyses and multigroup path analyses were carried out. Results: Dissociative experiences partially mediated the link between traumatic events and both types of skin-picking. The model was robust considering the conditions in which survey was filled out (pre-pandemic vs. pandemic). Conclusions: Traumatic life events and dissociative experiences are associated with both automatic and focused skin-picking regardless of pandemic conditions. Further studies are needed to understand mechanisms underlying the relationship between dissociation and skin-picking styles.